The dual role of autophagy in breast cancer stemness and treatment resistance - Anu Jayanthi Panicker (22330129) (2025)
Autophagy is a fundamental, highly conserved cellular process with a complex dual role in breast cancer progression and therapy resistance. Initially, autophagy functions as a tumor suppressor by maintaining genomic stability through clearance of damaged organelles and reducing oxidative stress, preventing tumor initiation. In established tumors, autophagy supports cancer cell survival under metabolic stress, sustains cancer stem cell stemness, and facilitates adaptation to hypoxia and nutrient deprivation in the tumor microenvironment. This pro-survival role enhances tumor growth, metastasis, and resistance to chemotherapy, radiotherapy, and targeted therapies. Autophagy extensively interacts with key signaling pathways governing cancer stem cell renewal and immune evasion, underscoring its multifaceted impact on tumor biology. Given its pivotal role, autophagy modulation via established inhibitors such as chloroquine alone and in combination with several other novel agents are under clinical investigation to investigate if its action that could be used to overcome therapy resistance and improve patient outcomes in breast cancer. Other Information Published in: Tissue and Cell License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.tice.2025.103279